Political Communication Strategy Of The Partai Keadilan Sejahtera (PKS) On Social Media Instagram @Pk_Sejahtera Against Anies Baswedan In The 2024 Presidential Election - Hana Radifa; Muhammad Prakoso Aji (UNIVERSITAS PAKUAN, 2024)
This study aims to analyze the political communication strategy of the Prosperous Justice Party (PKS) through Instagram social media in increasing Anies Baswedan's popularity in the 2024 Presidential Election. Using a qualitative research method based on netnography, data was obtained through observation of PKS's official Instagram account, semi-structured interviews, and sentiment analysis using the RapidMiner application. The results showed that PKS utilized Instagram to build Anies Baswedan's political image by uploading content based on relevant issues, narratives of change, and consistent use of hashtags. Sentiment analysis shows that the majority of comments are positive, reflecting the success of PKS's digital communication strategy. However, popularity on social media does not fully reflect electability in a national context, especially with the challenges of limited reach to rural voters and limited campaign funds. This research underscores the importance of integrating digital communication strategies with traditional approaches to strengthen candidate electability across different voter segments.